Rancang Bangun Mesin Pengaduk Pakan Ternak Bebek Melalui Pendekatan Antropometri Guna Mengurangi Waktu Proses Pengadukan di UD. Hadhita Jaya Makmur - Permana, Dylan Dias; Murnawan, Hery (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
UD. Hadhita Jaya Makmur was established in 1993 and located on Jalan S. Parman, Modopuro Village Rt.03, Rw.07, Mojosari District, Mojokerto Regency. The founder of this company is Mr. Drs.Munasrib, who is known in poultry farming activists, especially ducks. UD. Hadhita Jaya Makmur has ducks with a population of 3000 laying ducks, ducks at UD Hadhita Jaya Makmur produce about 2100 eggs every 2 days in December. UD. Hadhita Jaya Makmur strives to improve the quality of duck eggs by setting a target of feeding ducks as much as 500 kg every day for a population of 3000 ducks that are ready to lay eggs. Nevertheless, the use of manual methods in mixing duck animal feed ingredients has some negative impacts. The process of stirring duck animal feed takes quite a long time, which can reach 40 minute so that workers at UD. Hadhita Jaya Makmur experienced fatigue. One idea to be able to solve the problem is to design an animal feed mixer machine to provide significant results, providing results in accelerating the time of the 500kg per day animal feed stirring process which was originally at UD. Hadhita Jaya Makmur stirred animal feed ingredients in the process still using manual methods with a processing time duration of 43 minutes. After the design of the animal feed mixer machine, the process time of stirring animal feed ingredients to 15 minutes, the magnitude of the reduction in process time also affected the worker productivity index which was originally 19,3% to 55.5%.